Hopes and Challenges: The Analysis of The Role of Technology in Implementing Social Justice in Education for Indonesia's Golden Generation in 2045 - Suci Marselina; Gingga Prananda; Loso Judijanto; M.Amin Fatulloh; Dheo Rimbano; Muhammad Sukron Fauzi (The Future of Education Journal, 2024)
This study aims to comprehensively analyze the role of technology in achieving social justice in education. It will evaluate educational technology initiatives and their impact on improving education quality and equity of access. This type of research is a Systematic Literature Review, which is a systematic study that follows specific procedures to identify, evaluate, and synthesize all relevant research on a given topic. This method yields more comprehensive and reliable results. The findings regarding hopes and challenges in analyzing the role of technology in achieving social justice in education for Indonesia's Golden Generation in 2045 indicate that technology has significant potential to enhance accessibility, engagement, and personalized learning. However, challenges such as the digital divide, infrastructure quality, and limited teacher skills hinder the optimization of technology benefits. Additionally, social and cultural barriers, including resistance to change, are critical factors that need to be addressed to improve the acceptance of technology in education. Therefore, collaborative efforts involving the government, educators, and the community are needed to create an environment that effectively supports the use of technology, enabling all students to benefit and achieve social justice in education.